The preservation of significant Islamic architectural heritage of Al-Mustansiriya School, Baghdad City, Iraq - Akram,, Omar Khasro; Mohammed Jamil, Nada Fadhel; Franco, Daniel José; Ismail, Sumarni; Graca, Andreia (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Baghdad City is distinguished by its rich Islamic architectural heritage. Deterioration of heritage building values can affect the city itself as well as the country in general.This research highlights the issue that Al-Mustansiriya School, located in Baghdad City, is facing. There is no attention from local population neither governmental protection to its architectural heritage values. Therefore, there is a dire need to preserve the heritage school, aiming to increase not just tourism to the city, but also to the entire country. After the introduction of the background problem, this research presents the existing literature on Al-Mustansiriya School, highlighting the significant historical values, then summarizing the issues that it is facing. The methodology of this research uses a case study, following a qualitative method. This study contributes to the identification of the significant architectural element values of the place, proposing a theory on the protection of Islamic Architecture Heritage from the issues that Al-Mustansiriya in Baghdad City is facing and high-lights the important role of local organizations and archaeologists in preservation of heritage sites, with its recommendations. It helps on the protection and documentation of heritage values in Al-Mustansiriya, having a global impact towards humanity issues.